Evaluation of Wear, Mechanical and Metallurgical Properties of TIG Re-Melted Stellite 6 Cladded Over AISI-304 L Stainless Steel - Singh, Manjit; Handa, Amit; Sandhu, Sandeep Singh (Asian Review of Mechanical Engineering, 2014)
Stellite 6 is a cobalt based super alloy with major percentage of cr (27-32%), w(4-6%), c (0.9-1.4%) and other alloying elements like ni, fe, si, mn and mo. it is used for the improvement of wear resistance and mechanical properties of stainless steel engineering components used in harsh environment. the use of shielded metal arc welding (smaw) process for cladding of stellite 6 on stainless steel is getting attention due to high deposition rate and low dilution. initially bead on plate experiments were performed to optimize the single pass cladding process parameters i.e. current, electrode manipulation (stringer and weaving technique) and speed. 80 amp current with weaving technique were found to be optimum parameter for cladding with minimum dilution and maximum hardness with finer microstructure were found. these parameters were then used for multi pass multilayer cladding of stellite 6 on aisi 304 l. further the comparative study was performed for seven layer seven pass (slsp) and five layer five pass tig remelted (flfptr)stellite 6 cladding. the aim of this work is to analysis the effect of tig re-melting on wear, metallurgical and mechanical properties of aisi 304 l cladded with stellite 6.